The lock-up : a novel [large type] - Banville, John (Thorndike Press, a part of Gale, a Cengage Company, 2023)
"In 1950s Dublin, Rosa Jacobs, a young history scholar, is found dead in her car. Renowned pathologist Doctor Quirke and DI St. John Strafford begin to investigate the death as a murder, but it's the victim's older sister Molly, an established journalist, who discovers a lead that could crack open the case. One of Rosa's friends, it turns out, is from a powerful German family that arrived in Ireland under mysterious circumstances shortly after World War II. But as Quirke and Strafford close in, their personal lives may put the case--and everyone involved--in peril, including Quirke's own daughter"--